Prevalence of Medical Conditions among Dental Patients in Benghazi - Hamouda, Saleh; El Mehdawi, Huda (Libyan Journal of Dentistry, 2018)
Objectives: The aim of this study was to assess the prevalence of medical conditions and its relation to age and gender, among patients requesting dental treatment in private dental clinic, Benghazi University. Material and Methods: This prospective study was conducted on a total of 1192 patients reporting to the private dental clinic of Benghazi University, period from September, 2014 to April, 2016. The patient’s medical history was recorded on a predesigned preformat to find out the type of medical conditions in patients requiring dental treatment. The age range of the study population was from 15 years to 87 years, divided into seven age groups. Results were evaluated to see which medical problem is the most prevalent and to assess its relation to age and gender. Results: This study showed that out of 1192 dental patients, 711 were females and 481 were males. 380 (31.88%) were with medical problems. The five most prevalent conditions in descending order were endocrine diseases which constituted 35.26%, cardiovascular diseases which constituted 27.89%, gastrointestinal disorders (14.73%), hematological disorders (5.79 %) and respiratory conditions (5.79%). Conclusion: The results of the present study confirm that the prevalence of medical conditions is significant among patients requiring dental treatment. Therefore, a thorough medical history and careful clinical examination is mandatory before any dental procedure. It seems absolutely essential for dental practitioners to take a detailed medical history prior to any therapeutic procedure, as certain medical conditions, if unnoticed, will lead to unfavorable consequences and /or repercussions.